Dentists’ Awareness of Physical Therapy in the Treatment of Temporomandibular Disorders: A Preliminary Study - Inae C. Gadotti; Corey Hulse; Julia Vlassov; Derek Sanders; Daniela A. Biasotto-Gonzalez (Pain Research and Management)
Background. Physical therapy (PT) has been shown to be one of the most effective conservative treatments for temporomandibular disorders (TMD). Not all dentists are aware of the importance of the collaboration with physical therapists in the treatment of TMD pain. Objectives. To determine the awareness of dentists in Florida about the importance of PT for TMD pain and to create awareness related to collaborations. Methods. An online questionnaire was used. A contact list of dentists was obtained from the Florida Dental Association. The overall awareness and information on patient referral were presented per dentist specialty. Results. A total of 256 dentists completed the survey. Prior to the survey, 41% of the dentists reported not aware that PTs can treat TMD patients. Oral surgeons and orthodontists were more aware about PT compared to other specialties. After the survey, 81% of the dentists were more likely to refer their TMD patients to PT, and 80% were interested to know more about the benefits of collaborations. Conclusion. This study shows the lack of dentists’ awareness in Florida about the benefits of PT for TMD treatment. This study increased the awareness of the surveyed dentists in Florida about the benefit from a multidisciplinary approach.